Swallowing Disorders after Oral Cavity and Pharyngolaryngeal Surgery and Role of Imaging - Caterina Giannitto; Lorenzo Preda; Valeria Zurlo; Luigi Funicelli; Mohssen Ansarin; Salvatore Di Pietro; Massimo Bellomi (Gastroenterology Research and Practice)
Head and neck squamous cell carcinoma is the sixth most common cancer diagnosed worldwide and the eighth most common cause of cancer death. Malignant tumors of the oral cavity, oropharynx, and larynx can be treated by surgical resection or radiotheraphy with or without chemotheraphy and have a profound impact on quality of life functions, including swallowing. When surgery is the chosen treatment modality, the patient may experience swallowing impairment in the oral and pharyngeal phases of deglutition. A videofluoroscopic study of swallow enables the morphodynamics of the pharyngeal-esophageal tract to be accurately examined in patients with prior surgery. These features allow an accurate tracking of the various phases of swallowing in real time, identifying the presence of functional disorders and of complications during the short- and long-term postoperative recovery. The role of imaging is fundamental for the therapist to plan rehabilitation. In this paper, the authors aim to describe the videofluoroscopic study of swallow protocol and related swallowing impairment findings in consideration of different types of surgery.